The Potential Prognostic Role of Oligosaccharide-Binding Fold-Containing Protein 2A (OBFC2A) in Triple-Negative Breast Cancer - Wu, Qianxue; Tang, Xin; Zhu, Wenming; Li, Qing; Zhang, Xiang; Li, Hongyuan (Frontiers in Oncology, 2021)
Patients with triple-negative breast cancer (TNBC) have poor overall survival. The present study aimed to investigate the potential prognostics of TNBC by analyzing breast cancer proteomic and transcriptomic datasets. Candidate proteins selected from the National Cancer Institute’s Clinical Proteomic Tumor Analysis Consortium (CPTAC) were validated using datasets from Molecular Taxonomy of Breast Cancer International Consortium (METABRIC). Kaplan-Meier analysis and receiver operating characteristic (ROC) curve analysis were performed to explore the prognosis of candidate genes. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed on the suspected candidate genes. Single-cell RNA-seq (scRNA-seq) data from GSE118389 were used to analyze the cell clusters in which OBFC2A was mainly distributed. TIMER was used to verify the correlation between OBFC2A expression and immune infiltration. Clone formation assays and wound healing assays were used to detect the effect of OBFC2A expression on the proliferation, invasion, and migration of breast cancer cells. Flow cytometry was used to analyze the effects of silencing OBFC2A on breast cancer cell cycle and apoptosis. Six candidate proteins were found to be differentially expressed in non-TNBC and TNBC groups from CPTAC. However, only OBFC2A was identified as an independently poor prognostic gene marker in METABRIC (HR=3.658, 1.881-7.114), and OBFC2A was associated with immune functions in breast cancer. Biological functional experiments showed that OBFC2A might promote the proliferation and migration of breast cancer cells. On this basis, OBFC2A may be a potential prognostic biomarker and a therapeutic target for TNBC.